Cannon - Lai, Lee, 1993- (Drawn & Quarterly, 2025)
"We arrive to wreckage -- a restaurant smashed to rubble, with tables and chairs upended riotously. Under the swampy nighttime cover of a Montreal heat-wave, this is where we meet our protagonist, Cannon, dripping in little beads of regret sweat. She was supposed to be closing the restaurant for the night, but instead, well, she destroyed it. The mess feels a bit like a horror-scape -- not unlike the horror films Cannon and her best friend, Trish, watch together. Cooking dinner and digging into deep cuts of Australian horror films on their scheduled weekly hangs has become the glue in their rote relationship. In high school, they were each other's lifeline -- two queer second-generation Chinese nerds trapped in the suburbs. Now, on the uncool side of their twenties, the essentialness of one another feels harder to pin down. Yet, when our stoic and unbendingly well-behaved Cannon finds herself -- very uncharacteristically -- surrounded by smashed plates, it is Trish who shows up to pull her the hell outta there. In Cannon, Lee Lai's much anticipated follow-up to the critically-acclaimed and award-winning Stone Fruit, the full palette of a nervous breakdown is just a slice of what Lai has on offer. As Cannon's shoulders bend under the weight of an aging Gung-gung and an avoidant mother, Lai's sharp sense of humor and sensitive eye produce a story that will hit readers with a smash" --